Identification of Lactic Acid Bacteria in Milk and Milk Products with MALDI-TOF Mass Spectrometry - Miroslava Kačániová; Margareta Terentjeva; Lucia Godočíková; Czeslaw Puchalski; Simona Kunová; Maciej Kluz; Rafal Kordiaka; Peter Haščík (Scientific Papers Animal Science and Biotechnologies, 2023)
Recently, the Matrix assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) has been developed as vigorous method for the identification of microorganisms. In this study, the culturable population of lactic acid bacteria (LAB) from nonpasteurized milk and milk products was identified using the MALDI-TOF MS. Altogether, 20 samples of Slovak milk and milk products were tested, including 10 samples of milk and 10 samples of dairy products. The LAB were cultured on MRS agar at 30 °C. Gram-positive and catalase-negative strains were subjected to identification by the MALDI-TOF MS profiling. MALDI-TOF MS identification allowed the identification of three genera belonging to the LAB -  Lactobacillus, Lactococcus and Leuconostoc. Presence of Lactobacillus was found in 17, Leuconostoc in three and  Lactococcus only in one sample. Lactobacillus spp. was the most abundant genus and comprised 84% of all strains were isolated. Lactobacillus was mostly represented with four species:  Lactobacillus plantarum, L. acidophilus, L. ultunensis, L. casei. Our study shows that the MALDI-TOF MS could serve an important method in identidication of microorganisms for dairy industry needs.